Research progress on metal-organic frameworks in fluorescent detection of biomarkers - Wang, Han; Xing, Xiwen (Transactions on Environment, Energy and Earth Sciences, 2026)
Biomarkers act as "molecular probes" in disease diagnosis and play a pivotal role in disease diagnosis, prognostic evaluation, and monitoring of treatment efficacy. Traditional detection techniques like LC-MS/MS and ELISA come with limitations including high costs, prolonged testing durations, and elevated false-positive rates, these features have spurred the rapid advancement of fluorescent detection technologies. As an emerging class of fluorescent sensing materials, metal-organic frameworks (MOFs) possess unique structural designability, ultra-high specific surface area, and excellent biocompatibility, thereby exhibiting significant application potential in the field of biomarker fluorescent detection. This paper systematically reviews three major categories of biomarkers selected from a broad spectrum of biomarker types: pathogen-related biomarkers (anthrax biomarker pyridine-2,6-dicarboxylic acid (DPA)); disease metabolism-related biomarkers (carcinoid syndrome biomarkers 3-(2-aminoethyl)-1H-indol-5-ol (5-HT) and 2-(5-hydroxy-1H-indol-3-yl)acetic acid (5-HIAA), environmental toxin metabolite pyren-1-ol (1-HP), and amino acid metabolites 4-(2-aminoethyl)-2-methoxyphenol (3-MT) and histidine (His)); and nutrition and health-related biomarkers (2- (3, 4-dihydroxyphenyl)-3,5,7-trihydroxy-4H-chromen-4-one (Que)). Fluorescence detection technology based on metal-organic frameworks (MOFs) enables highly sensitive detection at the nM-μM level. Its mechanisms include host-guest recognition via hydrogen bonding and π-π stacking, photoinduced electron transfer (PET), and energy transfer (IFE, FRET), providing a technical foundation for the development of comprehensive detection systems. Although MOF-based fluorescent sensing technology holds great promise, it still faces challenges such as stability, biosafety, and application conversion. In the future, efforts should be made to optimize materials, improve safety assessment systems, and integrate equipment to accelerate the industrialization of MOF-based fluorescent sensing technology in precision medicine and disease diagnosis.